Analisis Bentuk Aransemen Lagu Anoman Obong Ciptaan Ranto Edi Gudel Untuk Paduan Suara Karya V. Mangunsongs (Jurnal Seni Musik, 2020)
The song Anoman Obong by Ranto Edi Gudel is a song that uses Javanese. The song was arranged into a choir format by V. Mangunsongs. The arrangement by V. Mangunsongs in the song Anoman Obong is unique, one of which is the combination of story and tragedy in the form of a SATB choir. This study aims to describe the form of the arrangement of the Anoman Obong song composed by Ranto Edi Gudel arranged for the choir by V. Mangunsongs. This study uses a qualitative approach with content analysis methods. Data collection was carried out through observation, interview and documentation methods. Interviews were conducted with competent speakers in this field as well as the aranger of Anoman Obong's song, namely V. Mangunsongs aka Eko Agus Kandung. The stages in analyzing data are data reduction, data presentation and conclusion. The validity of the data was obtained through the data source triangulation technique. Overall, the Anoman Obong song composed by Ranto Edi Gudel arranged for the choir by V. Mangunsongs has 111 bar rooms. The form of this arrangement is including free or group forms with Introductions (bar 1-24) - Part A (bar 25-35) - Part A '(bar 35-43) - Part B (bar 44-58) - Interlude (bar 58 -66) - Transition (bar 67-86) - Part B '(bar 87-101) - Postlude (bar 101-111). In this work, there are many changes in tempo and dynamic signs to support the atmosphere of Anoman Obong's story and tragedy. The results show that this work can transform a previously simple vocal song into a more complex choir.